Women’s Empowerment Through the Hidayah Women Farmers Group (KWT) in Improving Family Economic Resilience in Kenagarian Taram, Lima Puluh Kota Regency - Loviana L; Rahmat Fahmi (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines in-depth the practices of women's empowerment through the Hidayah Women's Farmers Group (KWT) in Taram Village, Lima Puluh Kota Regency. The approach used was descriptive qualitative, with data sources drawn from interviews, observations, and documentation of group activities. The results indicate that KWT Hidayah functions not only as a farming group but also as a social and economic learning space for women. Activities include horticultural crop cultivation, processing agricultural products into marketable products, and simple marketing practices. Impacts experienced by members include improved skills, additional income, and strengthening women's roles in the family economy. However, the group still faces obstacles in market access, capital, and product innovation.